2013
DOI: 10.3897/subtbiol.11.5170
|View full text |Cite
|
Sign up to set email alerts
|

Rana iberica (Boulenger, 1879) goes underground: subterranean habitat usage and new insights on natural history

Abstract: Reports of amphibians exploiting subterranean habitats are common, with salamanders being the most frequent and studied inhabitants. Anurans can occasionally be observed in caves and other subterranean habitats, but in contrast to salamanders, breeding had never been reported in a cave or similar subterranean habitat in Western Europe. Based on observations during visits to a drainage gallery in Serra da Estrela, Portugal, from May 2010 to December 2012, here we document: (i) first report of Rana iberica repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In green frogs (Pelophylax synklepton hispanicus (Bonaparte, 1839)) some adults were observed preying on high tree branches (Mori et al 2013). In artificial subterranean environments, the Iberian frog (Rana iberica Boulenger, 1879) has been observed climbing up the walls, probably looking for shelters (Rosa and Penado 2013). In our study, adults were observed more frequently being up higher along cave walls compared to juveniles (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In green frogs (Pelophylax synklepton hispanicus (Bonaparte, 1839)) some adults were observed preying on high tree branches (Mori et al 2013). In artificial subterranean environments, the Iberian frog (Rana iberica Boulenger, 1879) has been observed climbing up the walls, probably looking for shelters (Rosa and Penado 2013). In our study, adults were observed more frequently being up higher along cave walls compared to juveniles (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Frogs have been usually considered as an accidental presence in subterranean environments (Bressi and Dolce 1999), but recently many authors showed that some Anuran species can be quite common in these sites, selecting caves with specific environmental features (Köhler et al 2010, Rosa and Penado 2013, Biswas 2014, Lunghi et al 2014, Matavelli et al 2015. One of these species is the Italian stream frog Rana italica Dubois, 1987, which is endemic of Italian Apennines (Lanza et al 2006, Canestrelli et al 2008, Buono et al 2014, Sindaco and Grieco 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of fire salamander larvae in underground springs was recorded also in Romania (Ianc et al, 2012), Italy (Bressi & Dolce, 1999;Razzetti et al, 2001;Manenti et al, 2011) and Slovakia (Uhrin & Lešinský, 1997;Balogová & Uhrin, 2014, 2015 as well as in Portugal in the subspecies S. s. gallaica (Rosa & Penado, 2013).…”
Section: Population Datamentioning
confidence: 99%
“…However, most amphibians spend only a part of their lives in subterranean habitats intentionally or accidentally and are classified either as troglophiles or trogloxenes based on various criteria (Gunn, 2004). Furthermore, underground environments play an essential role as thermal refugia not only during winter but also for the persistence of some amphibians during drought and warm summer periods (e.g., Cimmaruta et al, 1999;Ficetola et al, 2012;Rosa & Penado, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These environmental similarities generally enable a similar faunistic composition in these two systems (natural and artificial cavities) (Peck 1988, Ferreira 2004, Bernardi et al 2010, 2011 in the same region. In this context, several taxa are common to both habitats, such as amphibians, arachnids, bats, crickets, moths and a large number of other invertebrates (Peck 1988, Gnaspini and Trajano 1994, Ferreira 2004, Bernardi et al 2010, 2011, Isaia et al 2011, Rosa and Penado 2013, Kurta and Smith 2014, Ueti et al 2015. Among these groups, the members of the order Opiliones are also a common component inside natural and artificial cavities.…”
Section: Introductionmentioning
confidence: 99%